Case report: Treatment of a patient with STEMI and cardiogenic shock caused by RCA originating from LAD - Niu, Qiang; Zhao, Yunhe; Li, Haiying; Wang, Qilei; Zhu, Haijun; Bi, Chenglong; Zhang, Hui; Wang, Jian; Cheng, Cheng; Song, Beibei; Jin, Chengwei; Lv, Ming; et al. (Frontiers in Cardiovascular Medicine, 2023)
The right coronary artery (RCA) originating from the left anterior descending artery (LAD) is a very rare variation of coronary artery anomaly. This kind of anomaly is usually considered to be clinically benign. Here, we present an acute myocardial infarction patient with a single coronary artery (SCA), in whom the LAD and RCA are both occlusive at the same time. He suffered from ventricular fibrillation, cardiogenic shock, and severe bradyarrhythmias many times. Fortunately, this patient survived from death through our effective medical procedures.